Female(s) body(ies) in Márcia X. “Lovely Babies” performance - Viotti, Andresa de Angeli; Benatti, Lucas (Farol, 2026)
Guided theoretically and methodologically by French-school Discourse Analysis—specifically the perspective of Michel Pêcheux and its intersections and shifts regarding art—this research is grounded in the discursive spaces surrounding the feminine, the body, and the female body. It aims to investigate the discursivization and meanings of the female body in the performance “Lovely Babies” by artist Márcia X. The video recording of the performance, originally staged in 1993, serves as the material for constructing the discursive corpus. Starting from the question of how the female body is discursivized and how it signifies meaning in “Lovely Babies,” the study reveals a discursivization of the female body’s representation within art that highlights the multiple meanings inherent in the woman-body-performance relationship.